Structure-Activity Relationships of Substituted 2,3,4,4a,5,10b-Hexahydro-benz[h]isoquinoline-6(1H)-ones as 5-HT2c Receptor Antagonists - Heinz Stadler; Jürgen Wichmann; Andrew J. Sleight; Michael Bös (CHIMIA, 2000)
A series of cis and trans configured 2,3,4,4a,5,10b-hexahydro-benz[h]isoquinoline-6(1H)-ones 2 were studied with respect to the binding affinity to the 5-HT2 subtype receptors. The influence of substituents in positions 7(R1), 8(R2) and 9(R3) on affinity and selectivity to 5-HT2A and 5-HT2c receptors and the preference of one diastereoisomer is discussed.